EDUKASI MANAJEMEN NYERI PADA KASUS OSTEOARTHRITIS LUTUT PADA LANSIA DI DESA GONDANG SARI KIRINGAN BOYOLALI - Qoriq Nur Azizah; Ginda Zaura Finanda; Malida Arneta Nor Vaiszhah; Maya Mukti Habbil Hasanah; Putra Aditya Utama; Putri Frida Nur Aulia; Salsa Zulaykha Yasmine; Valentino Singgih Pangestu Wely; Nur Agung Martopo (Jurnal Padamu Negeri, 2026)
Knee osteoarthritis is one of the degenerative diseases commonly experienced by the elderly and can cause symptoms such as pain, joint stiffness, and limitations in functional activities. Limited knowledge among the elderly regarding the causes, symptoms, and management of knee osteoarthritis may worsen the their condition and reduce their quality of life. Therefore, this Community Service Program was conducted in Gondang Sari Village, Kiringan, Boyolali, with the aim of increasing the elderly’s knowledge about knee osteoarthritis and independent pain management. The activity involved 25 elderly participants and was carried out through health education and demonstrations of simple physiotherapy exercises, including quadriceps setting, hamstring setting, hamstring stretch, leg extension, calf stretch, and calf raise. Evaluation was conducted using pre-test and post-test questionnaires to measure the improvement in participants’ knowledge. The results showed an increase in participants’ understanding after the educational intervention. In the pre-test, 100% of participants did not understand knee osteoarthritis, while in the post-test 76% understood the material and 24% had moderate understanding. These findings indicate that health education and physiotherapy exercises effectively improve the elderly’s knowledge and support independent pain management, thereby helping to improve their quality of life.